2009
DOI: 10.1063/1.3067872
|View full text |Cite
|
Sign up to set email alerts
|

Spin-lattice coupling in multiferroic Pb(Fe1/2Nb1/2)O3 thin films

Abstract: We have made magnetization and x-ray diffraction measurements on an epitaxial Pb(Fe1/2Nb1/2)O3 200 nm film. From the temperature dependence of the out-of-plane lattice parameter we can assign a Burns' temperature at Td ~ 640 K, a temperature at T* ~ 510 K, related to the appearance of static polar nanoregions, and an anomaly occurring at 200 K. The latter is precisely the N\'eel temperature TN determined from magnetization and points to spin-lattice coupling at TN ~ 200 K. We also observe "weak ferromagnetism"… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Though the physics of ferroelectricity and magnetoelectric (ME) coupling in AMnO 3 is very exciting, they are not useful for practical applications at room temperature since the magnetic field-induced ferroelectric polarization is rather small and the magnetic transition occurs mostly below the liquid nitrogen temperature. The ferrimagnetic magnetic transition of PbFe 0.5 Nb 0.5 O 3 is also below 300 K. 8 The high values of ferroelectric Curie temperature (T C(FE) ~ 836 °C) 9,10 and antiferromagnetic transition temperature (T N ~ 370 °C) 11 found in BiFeO 3 make this compound more attractive. Ferroelectricity in BiFeO 3 is driven by the sterochemical 2 activity of 6s 2 lone pair of Bi 3+ ions, whereas the Fe ions order antiferromagnetically.…”
Section: Introductionmentioning
confidence: 99%
“…Though the physics of ferroelectricity and magnetoelectric (ME) coupling in AMnO 3 is very exciting, they are not useful for practical applications at room temperature since the magnetic field-induced ferroelectric polarization is rather small and the magnetic transition occurs mostly below the liquid nitrogen temperature. The ferrimagnetic magnetic transition of PbFe 0.5 Nb 0.5 O 3 is also below 300 K. 8 The high values of ferroelectric Curie temperature (T C(FE) ~ 836 °C) 9,10 and antiferromagnetic transition temperature (T N ~ 370 °C) 11 found in BiFeO 3 make this compound more attractive. Ferroelectricity in BiFeO 3 is driven by the sterochemical 2 activity of 6s 2 lone pair of Bi 3+ ions, whereas the Fe ions order antiferromagnetically.…”
Section: Introductionmentioning
confidence: 99%
“…5 (c). Peng et al 41 reported the temperature evolution of the lattice parameter of PFN film grown by PLD technique (similar to us). Here we reproduced the lattice constant behavior of PFN film with the reported value of Peng et al (Fig.…”
Section: C2 Phonon Dynamics At the Regime Of Negative Thermal Expanmentioning
confidence: 99%
“…instead it undergoes thermal contraction 41 . In such a case the phonon energies should increase (as observed, see Fig.5).…”
Section: C2 Phonon Dynamics At the Regime Of Negative Thermal Expanmentioning
confidence: 99%
“…Consequently, it is reasonable to invoke magnetostriction in its switching dynamics at higher temperatures in an applied field H. PFN. Magnetic and electrical studies of PFN and of PFN mixed with PbMg 1/2 W 1/2 O 3 by Peng et al [40][41][42] revealed several important things: PFN can be prepared in a single phase, without any pyrochlore or other minor phases; it exhibits relaxor behavior characterized by antiferromagnetic clusters and by two equations-a standard Vogel-Fulcher Equation describing a characteristic relaxation frequency…”
Section: Lead-iron Perovskitesmentioning
confidence: 99%
“…400 K because of spin clustering. [41][42][43][44] This has been well studied in pure PFN via magnetic resonance. Such cluster systems are not readily amenable via conventional density functional technique theory but might be suited to the type of calculation published by Bersuker and colleagues.…”
Section: Lead-iron Perovskitesmentioning
confidence: 99%